Divergent changes of the elevational synchronicity in vegetation spring phenology in North China from 2001 to 2017 in connection with variations in chilling. (13th May 2021) - Dai, Junhu; Zhu, Mengyao; Mao, Wei; Liu, Ronggao; Wang, Huanjiong; Alatalo, Juha Mikael; Tao, Zexing; Ge, Quansheng
Abstract: Mountain ecosystems are sensitive to climate change, and vegetation phenology provides one of the best signals to exemplify ecosystem responses to climate change. Vegetation phenology of mountain ecosystems is usually characterized with an elevational pattern, with the growing season starts earlier and ends later in lower versus higher elevations. With climate change, this elevational gradient of vegetation phenology is likely to shift as well. However, both the patterns and the underlying driving forces for potential changes in this elevational gradient of vegetation phenology are still unclear. Here, we used 500‐m resolutioned normalized difference vegetation index (NDVI) data from Moderate Resolution Imaging Spectroradiometer (MODIS) for the period of 2001 to 2017 to investigate changes in the start of growing season (SOS) along the elevational gradient for six mountains in northern China dominated by broadleaf deciduous forests. We found that while SOS consistently advanced for most of the pixels, the elevational lapse rate of SOS (SE ) showed various trends for different mountains. Specifically, SE showed a significant ( p ‐value < .05) decreasing trend for the two southernmost mountains, indicating an increasing elevational synchronization in SOS. However, such phenological synchronization was not found in other temperate mountains. As warming has caused relatively consistent increases in heat forcing across different elevations and among different mountains but has led to highly various changes in chilling hours between high and low elevations, we suggested that the distinctive pattern in elevational synchronicity of spring phenology between southern and northern mountains in temperate China was primarily due to their different recent changes in chilling hours. Our work provides a novel key hypothesis for explaining the divergent changes in elevational gradients of vegetation phenology that can be tested in other regions for mountain ecosystems. Abstract : Change in elevational synchronicity of vegetation spring phenology for six mountains in North China from 2001 to 2017.